Принципи розробки змісту навчальних посібників для підготовки вчителів природничо-математичних дисциплін - Сосницька, Наталя Леонідівна; Sosnytska, Natalia; Сосницкая, Наталья Леонидовна (My University, 2016)
UK: У статті визначено та теоретично обґрунтовано загальні та специфічні принципи розробки змісту навчальних посібників для підготовки вчителів природничо-математичних дисциплін, зокрема: пріоритетності педагогічного підходу; відповідності кредитно-трансферній системі організації навчального процесу; позитивної мотивації та сприятливого емоційного навчання, а також практичної зорієнтованості. Зазначено підхід до врахування означених принципів при розробці навчальних посібників, який полягає в обранні домінуючого принципу згідно з дидактичною метою та відповідною структурою змісту навчального засобу. Наведено приклади застосування специфічних принципів. RU: В статье определены и теоретически обоснованы общие и специфические принципы разработки содержания учебных пособий для подготовки учителей естественно-математических дисциплин, в частности: приоритетности педагогического подхода; соответствия кредитно-трансферной системе организации учебного процесса; положительной мотивации и благоприятного эмоционального обучения; практической ориентированности. Отмечен подход к учету указанных принципов при разработке учебных пособий, который заключается в выборе доминирующего принципа согласно дидактической цели и соответствующей структуры содержания учебного средства. Приведены примеры использования специфических принципов. EN: In the article attentions is paid to the problem of providing educational establishments by qualitative textbooks. The solving of this problem partially depends on their accordance to state standards of education and features of credit-transfer system of educational process organization. The aim of the article is defining and theoretical grounding of general and specific principles of development of the content of textbooks for training of teachers of nature-mathematical disciplines. There have been defined general (scientific, accessibility, problem, visibility, system) and distinguished specific principles of development the content of textbooks for training of teachers of nature-mathematical disciplines, in particular: priority of pedagogical approach, accordance of credit-transfer system to organization of educational process, positive motivation and conductive emotional reaching and practical orientation. There have been grounded the approach to accounting the giving principles during development of textbooks which is in the choice of dominant principle according to didactic aim and appropriate structure of the content of educational means. There have been given examples of using specifically principles as for textbooks: “The historical aspects of school physics course content”, “General physics. Electrics and magnetism”, “The basis of introduction of innovational technologies of physics teaching”, “The technical means of teaching”. The further research is to development the content of textbooks for training of specialists of giving speciality to activity in the conditions of professional and technical educational establishments.
Принципы разработки содержания учебных пособий для подготовки учителей естественно- математических дисциплин
The principles of development the content of textbooks for training of nature-mathematical disciplines
Keywords: навчальний посібник; загальні принципи; природничо-математичні дисципліни; учебное пособие; принципы общие; естественно-математические дисциплины; textbooks; general (specific) principles; nature-mathematical disciplines